Efecto causado por la introducción de machos esterilizados por radiación gamma, en una población normal de moscas del Mediterráneo (Ceratitis capitata) - Katiyar, K.P.; VALERIO, J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Mating competitiveness of gamma sterilized Medfly males was studied in the laboratory by confining together treated and normal flies in different proportions in small cages. Although the fertility of normal females was reduced at every level of overflooding tested, the reduction was lower than expected in every case. This indicates that the radiation decreases the mating vigor of the treated males. Maximum reduction of 89 percent in female fertility was recorded when normal flies were overflooded 39 times with sterile ones.